Gender Equality in the Post‐2015 Development Agenda: Lessons from the MDGs. (2nd September 2013) - Sen, Gita
Abstract: This article addresses some central issues for the Post‐2015 Development Agenda from a Southern perspective on gender equality and women's human rights. To answer this question, it first examines what lessons can be learned from the decade or so of implementation of the MDGs. The article focuses on two 'meso' challenges: breaking down issue silos, and integration/participation. It argues that progress towards gender equality will depend on whether the larger development framework addresses central issues such as the growing inequality, informalisation and precariousness of work and incomes that have gone hand in hand with the globalisation of the past three decades. Within a framework that tackles head on the causes and consequences of rising global and national inequality, progress on women's rights requires recognition that gender inequality is pervasive across multiple and intersecting issues. Effectively addressing women's needs and rights requires the building of bridges across policy silos through the integration of issues and participation by women.